The Genome of the Medicinal Macrofungus Sanghuang Provides Insights Into the Synthesis of Diverse Secondary Metabolites - Shao, Ying; Guo, Hongwei; Zhang, Jianping; Liu, Hui; Wang, Kun; Zuo, Song; Xu, Pengfei; Xia, Zhenrong; Zhou, Qiumei; Zhang, Hanghang; Wang, Xiangqing; Chen, Anhui; et al. (Frontiers in Microbiology, 2020)
The mushroom, Sanghuang is widely used in Asian countries. This medicinal fungus produces diverse bioactive compounds and possesses a potent ability to degrade the wood of the mulberry tree. However, the genes, pathways, and mechanisms that are involved in the biosynthesis of the active compounds and wood degradation by Sanghuang mushroom are still unknown. Here, we report a 34.5 Mb genome—encoding 11,310 predicted genes—of this mushroom. About 16.88% (1909) of the predicted genes have been successfully classified as EuKaryotic Orthologous Groups, and approximately 27.23% (665) of these genes are involved in metabolism. Additionally, a total of 334 genes encoding CAZymes—and their characteristics—were compared with those of the other fungi. Homologous genes involved in triterpenoid, polysaccharide, and flavonoid biosynthesis were identified, and their expression was examined during four developmental stages, 10 day old and 20 day old mycelia, one year old and three year old fruiting bodies. Importantly, the lack of chalcone isomerase 1 in the flavonoid biosynthesis pathway suggested that different mechanisms were used in this mushroom to synthesize flavonoids than those used in plants. In addition, 343 transporters and 4 velvet family proteins, involved in regulation, uptake, and redistribution of secondary metabolites, were identified. Genomic analysis of this fungus provides insights into its diverse secondary metabolites, which would be beneficial for the investigation of the medical applications of these pharmacological compounds in the future.